Pemberdayaan Masyarakat Dalam Bidang Linkungan, Ekonomi dan Kelembagaan - Permana, Sulwan; Hadi, Muhamad Rizal Nurul; Suparman, Tegar Radiansyah; Sulastri, Dewi; Khaerunisa, Nisrina; Maulina, Wina Senja; Purnama, Alpin; Maulana, Mochamad Dilla; Giandhani, Mochammad Rizky; Nurahman, Zamzam; Munawar, Arby Muhyi; Firdausa, Muhamad Arga; Firzatullah, Belva Prana; Mubarok, Abil Miftahul; Maelani, Rega; Sukma, Ersa Hermalia; Aminah, Siti Nur; Fardiansyah, Bagas; Hilmayanti, Hilmayanti; Zaman, Muhammad Badru (Jurnal PkM MIFTEK, 2023)
At this time there are many problems faced by the community, especially in facing challenges in life in the future. Recent issues that are often faced regarding digitalization, environment, economy and institutions. The purpose of this KKN-Thematic is to empower the community in Wanamekar Village, Wanaraja District, especially hamlet 2 and hamlet 3 according to the field of cultivation. Digitalization is currently being driven by the government so that people are literate about the benefits and understand technology now, as was done by the Garut Institute of Technology KKN-Thematic participants in Wanamekar Village, Wanaraja District. The main problems in digital literacy start from people often misusing technology, difficult business development, ethics in social media. Apart from that, the issue of recognizing the environment by making biopore wells, socialization on making eco enzyme about processing organic waste into soap, applying visual displays about prohibitions and warnings, giving directions about online business for MSME business actors in Wanamekar Village, especially in hamlet 2 and hamlet 3. And National Computer-Based Assessment of elementary school students.